2014
DOI: 10.3109/14756366.2014.940932
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new isoxazoline derivatives from harmine and evaluation of their anti-Alzheimer, anti-cancer and anti-inflammatory activities

Abstract: In our study, a series of new harmine derivatives has been prepared by cycloaddition reaction using various arylnitrile oxides and evaluated in vitro against acetylcholinesterase and 5-lipoxygenase enzymes, MCF7 and HCT116 cancer cell lines. Some of these molecules have been shown to be potent inhibitors of acetylcholinesterase and MCF7 cell line. The greatest activity against acetylcholinesterase (IC50 = 10.4 µM) was obtained for harmine 1 and cytotoxic activities (IC50 = 0.2 µM) for compound 3a. Two derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…The prepared derivatives have been shown to be inactive to moderately active and the noted per cent inhibitions of most of them ranged from 3.3 ± 1.2% (compound 2e ′) to 53.1 ± 4.8% (mixture 2f+f ′) at 200 μ m . These results were in agreement with one of our earlier works that described the anti‐5‐lipoxygenase activity of certain isoxazolines prepared from harmine . The results of the above work have shown that cycloadducts with isoxazolines bearing a phenyl, a 4‐methylphenyl, a 4‐methoxyphenyl and a 4‐chlorophenyl have been found to be inactive .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The prepared derivatives have been shown to be inactive to moderately active and the noted per cent inhibitions of most of them ranged from 3.3 ± 1.2% (compound 2e ′) to 53.1 ± 4.8% (mixture 2f+f ′) at 200 μ m . These results were in agreement with one of our earlier works that described the anti‐5‐lipoxygenase activity of certain isoxazolines prepared from harmine . The results of the above work have shown that cycloadducts with isoxazolines bearing a phenyl, a 4‐methylphenyl, a 4‐methoxyphenyl and a 4‐chlorophenyl have been found to be inactive .…”
Section: Resultssupporting
confidence: 92%
“…These results were in agreement with one of our earlier works that described the anti-5-lipoxygenase activity of certain isoxazolines prepared from harmine. [25] The results of the above work have shown that cycloadducts with isoxazolines bearing a phenyl, a 4-methylphenyl, a 4-methoxyphenyl and Table 1 5-lipoxygenase inhibition capacity (per cent inhibition (%)) and cytotoxicity (HCT-116, IGROV-1 and OVCAR-3 cells lines) (IC 50 (lM)) of (-)-deltoin 1 and its derivatives 2a,a 0 -f,f 0 and 3a,a 0 -e,e 0 The aziridine derivatives, except 3c,c 0 , have shown a moderate cytotoxic activity against the ovary cell lines IGROV-1 and OVCAR-3 with IC 50 values ranging from 31.0 AE 2.0 to 71.0 AE 2.6 lM. This difference is due to the selectivity of the products tested against these cancer cell lines.…”
Section: -Lipoxygenase Inhibitorymentioning
confidence: 99%
See 1 more Smart Citation
“…discuss the inhibitory activity of harmine and its isoxazoline derivatives (Figure ) against AChE. Harmine and its isoxazoline derivatives show inhibition of AChE, and harmine shows the best inhibitory activity with an IC 50 value of 10.4 μ m …”
Section: Discussionmentioning
confidence: 99%
“…From ancient times, this alkaloid drew increasing interest due to its diverse pharmacological and biological activities 11 . It is known to be anti-acetylcholinesterase, antimicrobial, antifungal and cytotoxic 12 . The latest research showed that harmine can inhibit the breast cancer protein BCRP so it was used as resistance to anticancer drugs 13 .…”
Section: Introductionmentioning
confidence: 99%